ORGANIZATION OF REFINED PRODUCTS SALES IN KAZAKHSTAN - Shoshanov Saken Bakhytzhanovich; Makhanov Sagat Sultanbekovich; Salykova Leila Nurtleuovna; Petr Hajek (Scientific Journal of Pedagogy and Economics, 2021)
The article presents the main theoretical and methodological approaches to the sale of refined products. The views of scientists and economists on the sales of refined products and its categories are considered. Organization schemes of petroleum products sales on domestic and world markets, multilevel marketing system, routes of product movement (logistics chain of product movement) have been substantiated. The main documents (futures), risk insurance (hedging), planning the organization of sales of petroleum products, the impact of marketing programs on the choice of sales channel are considered. The article presents the formation of sales channels for petroleum products in vertically integrated oil companies. The tasks for timely provision of consumers with petroleum products have been clarified. The optimal choice of efficient schemes for cargo transportation of refined products, logistics schemes for their transportation and temporary storage, and rationality of transit forms of delivery of oil products to consumers are indicated. The main goals of achieving optimal sales systems for petroleum products by vertically integrated oil companies are revealed. The possibility of having special divisions for the sale and export of refined products by large oil companies is justified. The analysis of indicators of demand and supply of petrochemical products on the world markets with the author’s positions on the current situation on the world oil markets in connection with the coronavirus pandemic. The analysis and assessment of production and consumption of basic petroleum products on the domestic markets of Kazakhstan is given. As a separate example, the analysis of diesel fuel consumption by regions and sectors of the national economy of Kazakhstan was carried out.